The functional role of cellular senescence during vascular calcification in chronic kidney disease - Fang, Ya-Ping; Zhao, Yu; Huang, Jia-Yi; Yang, Xin; Liu, Yan; Zhang, Xiao-Liang (Frontiers in Endocrinology, 2024)
Vascular calcification (VC) has emerged as a key predictor of cardiovascular events in patients with chronic kidney disease (CKD). In recent years, an expanding body of research has put forth the concept of accelerated vascular aging among CKD patients, highlighting the significance of vascular cell senescence in the process of VC. Within the milieu of uremia, senescent vascular endothelial cells (VECs) release extracellular microvesicles (MV) that promote vascular smooth muscle cells (VSMCs) senescence, thereby triggering the subsequent osteogenic phenotypic switch and ultimately contributing to the VC process. In addition, senescent vascular progenitor or stem cells with diminished ability to differentiate into VECs and VSMCS, compromise the repair of vascular integrity, on the other hand, release a cascade of molecules associated with senescence, collectively known as the senescence-associated secretory phenotype (SASP), perpetuating the senescence phenomenon. Furthermore, SASP triggers the recruitment of monocytes and macrophages, as well as adjacent VECs and VSMCs into a pro-adhesive and pro-inflammatory senescent state. This pro-inflammatory microenvironment niche not only impacts the functionality of immune cells but also influences the differentiation of myeloid immune cells, thereby amplifying the reduced ability to effectively clear senescent cells of senescent macrophages, promoted calcification of VSMCs. The objective of this paper is to provide a comprehensive review of the contribution of vascular cell senescence to the emergence and advancement of VC. Gaining a comprehensive understanding of the involvement of cellular senescence within the vessel wall is pivotal, especially when it comes to its intersection with VC. This knowledge is essential for advancing groundbreaking antiaging therapies, aiming to effectively mitigate cardiovascular diseases.AKI ALP APCs CaSRs CDKI CKD EndMT MAC MSCs MV NMN NRF2 PWV RS SASP SAHF SIPS VC VECs VSMCs adventitial fibroblasts acute kidney injury alkaline phosphatase adventitial pericytes calcium-sensing receptors cyclin-dependent kinase inhibitor chronic kidney disease endothelial-to-mesenchymal transition medial arterial calcification mesenchymal stromal cells microvesicles nicotinamide mononucleotide nuclear factor erythroid 2-related factor 2 pulse wave velocity replicative senescence senescence-associated secretory phenotype senescence-associated heterochromatin foci stress-induced premature senescence Vascular calcification vascular endothelial cells vascular smooth muscle cells